Sustainable Hospitality in Emerging Cities: Assessing Green Practices in Manado Hotels - Yovanca Yully Feniaty Koondoko; Daniel Pandu Mau; Masrun; Lalu Mahsar; I Gusti Ngurah Oka Widjaya; Enesi Chukwuemeka Majebi (Faculty of Economics and Business, University of Mataram, 2026)
This study examines sustainable hospitality practices in Manado, focusing on how green practices influence service quality, customer satisfaction, and behavioural intentions in an emerging urban tourism context. Adopting a mixed-methods approach, the research integrates Structural Equation Modelling (SEM) with qualitative managerial insights to provide a comprehensive assessment of sustainability implementation in the hotel sector. Data were collected from 247 hotel guests and complemented by interviews with hotel managers. The findings reveal that green practices comprising energy efficiency, water conservation, waste management, and environmental awareness have a significant positive effect on perceived service quality, which in turn enhances customer satisfaction and behavioural intentions such as revisit intention and word-of-mouth. While green practices also directly influence behavioural intentions, their strongest impact occurs indirectly through service quality and satisfaction, highlighting the importance of integrating sustainability into the overall service experience. Qualitative results indicate that sustainability adoption in Manado is still in a transitional phase, often driven by cost efficiency rather than a fully institutionalised environmental strategy. This study contributes theoretically by extending the resource-based view and service quality frameworks within the context of sustainable hospitality, and by emphasising the role of contextual factors in emerging destinations. Practically, the findings suggest that hotels should position sustainability as a strategic value driver rather than merely an operational cost-saving measure. Overall, the study underscores the importance of aligning hospitality development with sustainability principles to enhance competitiveness and support long-term tourism growth